FeCl3/Montmorillonite K10 as an efficient catalyst for solvent-free aza-Michael reaction between amine and alpha,beta-unsaturated compounds - Choudhary, Vasant R.; Dumbre, Deepa K.; Patil, S. K. (RSC Advances, 2012)
A highly efficient, inexpensive and greener protocol for aza-Michael addition reaction of different aromatic and aliphatic/cyclic amines to alpha,beta-unsaturated compounds using a FeCl3/MontK10 catalyst under solvent-free conditions has been developed. The Michael addition products are obtained in good to excellent yields. The catalyst was insensitive to moisture and it also showed excellent reusability in the reaction. Its high activity is attributed mostly to redox properties of FeCl3.

Mesoporous, ligand free Cu-Fe solid catalyst mediated CS cross coupling of thiols with aryl halides - Dumbre, Deepa K.; Selvakannan, P. R.; Patil, S. K.; Choudhary, Vasant R.; Bhargava, Suresh Kumar (Applied Catalysis A-General, 2014)
Solid catalyst derived from Cu-Fe hydrotalcite was demonstrated to be a novel, ligandless, efficient and environmentally greener catalyst for the synthesis of diaryl sulfurs from the C-S cross coupling reaction of substituted thiols with different aryl halides. This catalyst has shown higher product yield in the presence of dimethylformamide (as a solvent) and K2CO3 (as a base) at 120 C. Influence of different solvents and bases on the product yield has also been investigated. The catalyst can be easily separated from the reaction mixture, simply by filtration and reused several times without a significant loss of its activity. The catalyst has been fully characterized for its surface and bulk properties and the mesoporous CuO:Fe2O3 phase was attributed for its catalytic activity towards S-arylation reactions. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: C-S cross coupling; Cu-Fe-hydrotalcite; S-arylation